Otorhinolaryngology. Issue 892 (1st February 2000) - Weir, Neil
Abstract : Otorhinolaryngology, a product of the early 20th century, developed from the joining together of the separate departments of otology, whose practitioners were surgeons, and laryngology which was managed by physicians who also treated diseases of the nose and chest. The 20th century opened with brave attempts to perform skilful surgery under conditions of primitive anaesthesia and no antibiotics. The stimulus of two world wars led to significant advances in technology and greater opportunities to explore new and resurrect old surgical procedures. The discovery of antibiotics saw an end to acute mastoiditis and the complications of otitis media and sinusitis, as well as a decline in the number of tonsillectomy and adenoidectomy operations. Over the last 30 years the specialty has undergone dramatic development and has taken advantage of new advances in endoscopy, microsurgery, the use of lasers, cytotoxic drugs, flap reconstruction and microchip technology. During the same period, although still calling themselves otorinolaryngologists, individual surgeons have subspecialised in otology, otoneurosurgery and skull-base surgery, head and neck surgery, phonosurgery, rhinology and facioplastic surgery, and paediatric otothinolaryngology. Each of these subspecialties has its own societies and specialist journals.